Manifestations of the Algerian legislator’s interest in the environment - Benlabidi, Malek; Benchabane, Ali (Journal of Human Sciences, 2022)
The algerian state has mode great strides in the field of preparing and implementing ou environmental legal arsenal which it started by joining the international effort and has gone begond with global interest in environmental issues. It also condified this interest in the different constitutuions, which shows the great importance. In order to implement these policies, the institutional frame work has been updated and eveloped as algeria supported its constitutional and legal efforts with an institutional effort culminated by the establisement of a special ministry for the environment after the stage of instability and dealt with varios ministerial departements, and this is due to the government’s lack of interest in environmental policy and the failure of development plans that neglect to include environmental considerations in their development and economic projects .